Behavior analysts' perceptions of the population specificity or comprehensiveness of autism treatments. (2nd January 2021) - Campbell, Elizabeth A.; Schreck, Kimberly A.; Zane, Thomas
Abstract: The basic philosophy of radical behaviorism provides foundations for behavioral intervention applications in applied behavior analysis (ABA) across a variety of populations and human behaviors. However, as ABA increases in popularity for people with autism, many people perceive that ABA resembles other non‐research‐supported interventions which market themselves almost exclusively for autism. This study evaluated the extent to which behavior analysts perceived scientifically supported treatments (e.g., ABA) and non‐scientifically supported treatments as population‐specific or as comprehensively applicable across populations. Behavior analysts ( N = 876) completed an online survey which indicated that approximately 3/4 of behavior analysts reported ABA as comprehensively effective for all people. Treatments without scientific support also were ranked more often or as effective as ABA for specific populations (i.e., intellectual and developmental disabilities, autism, severe behavior problems, adults, and children). Results indicated a continuing need to emphasize the education and requirements of radical behaviorism as the scientific foundations of ABA.